Traction-bed-assisted reduction and double-plate fixation for treatment of comminuted femoral intertrochanteric fractures with coronal split - Hu, Liangcong; Xie, Xudong; Wang, Tiantian; Mi, Bobin; Xue, Hang; Lin, Ze; Xiong, Yuan; Hu, Yiqiang; Zhou, Wu; Cao, Faqi; Liu, Guohui (Frontiers in Surgery, 2022)
Background: Coronal comminuted femoral intertrochanteric fractures are a special type of fractures that easily lead to internal fixation failure, and the current internal fixation techniques are still controversial. This study aim to evaluate the effect of traction bed-assisted reduction and double plate fixation in the treatment of comminuted femoral intertrochanteric fractures with coronal split. Method: A retrospective analysis of the clinical data of 83 patients with intertrochanteric fractures with coronal split in our department from December 2017 to November 2019, of which 43 cases received traction bed-assisted reduction and double plate internal fixation (experimental group), 40 cases received traction bed assisted reduction and PFNA fixation treatment (control group). The basic conditions of patients, perioperative indicators, and follow-up indicators of the two groups were collected. Results: The reduction and operation time of the experimental group was significantly shorter than that of the control group (P<0.05). The Harris score of the hip joint at 3 months and the last postoperatively was significantly better than that of the control group, with significant statistical difference (P<0.05). There was no significant difference in terms of preoperative hemoglobin (Hb), intraoperative blood loss, first postoperative hemoglobin (Hb), incidence of wound infection at 14 days postoperative, first time to the ground after surgery, Harris score 2 weeks after surgery, fracture healing time and incidence of complications between the two groups(P>0.05). Conclusion: The use of a traction bed to assist reduction and double plate fixation for the treatment of intertrochanteric fractures combined with coronal split can shorten the reduction and operation time, improve the reduction effect and obtain better long-term hip joint function.